Infiltration-Induced Landslide: An Application of Richards Equation - Timsina, Ramesh Chandra (Journal of Nepal Mathematical Society, 2024)
In this work, we incorporate the solution of Richards equation in infinite slope model to locate the potential landslide hazards area and prediction of landslide hazards induced by heavy rainfall, continuously precipitation and redistribution. Firstly, we modeled the Richards equation in cylindrical coordinate with axial symmetry and use Kirchhoff ’s transformation to linearize it. With Kirchhoff ’s transformation the nonlinear axi-symmetric model is transformed into the nonlinear parabolic equation. Because of its high non-linear properties, analytical solutions of Richards equation are rare and limited for particular cases with hardly reliable. To solve the equation numerically, different approximation techniques as FDM, FVM are used on the prescribed model. Since, the landslide hazards problems are accelerated by safety factor which are related to the forces that restrain the surface from failure and endow the surface to smash. Hence to evaluate the safety factor we use the infinite slope model characterized with moisture content, pressure head in variably saturated (unsaturated) soils. The attachment of Richards equation along with the infinite slope model in the expression of safety factor which helps to explore the surface failure condition for different soils for their different physical characteristic including precipitation, infiltration, redistribution and moisture content.